PENELITIAN ARKEOLOGI BAWAH AIR DI INDONESIA TANTANGAN, PELUANG, DAN ARAH KEBIJAKAN PENELITIAN ARKEOLOGI MARITIM - Siswanto (BRIN, 2010)
In Indonesia, underwater archaeology as a part of maritime study seems to be isolated, because the study has not yet made significant contribution to the understanding of maritime life ways in the archipelago. Various archaeological data needed to reveal the history of human settlement, insular trade, maritime history, migration, and other aspects of maritime culture in the archipelago are still concealed at the bottom of the sea or rivers. On the other hand, the development of underwater archeology in Indonesia is still left far behind compared to other Southeast Asian countries, so the abundant underwater archaeological data are still unreachable. So far, the existing underwater archaeology activities carried out within this largest archipelagic country are still aimed at exploring underwater 'treasure